2020
DOI: 10.1017/aog.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of turbulence transfer in the near-surface layer over the Antarctic sea-ice surface from April through November in 2016

Abstract: The surface energy budget over the Antarctic sea ice from 8 April 2016 through 26 November 2016 are presented. From April to October, Sensible heat flux (SH) and subsurface conductive heat flux (G) were the heat source of surface while latent heat flux (LE) and net radiation flux (R n ) were the heat sink of surface. Our results showed larger downward SH (due to the warmer air in our site) and upward LE (due to the drier air and higher wind speed in our site) compared with SHEBA data. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The roughness lengths for humidity and temperature were calculated as a function of the friction velocity and z 0 according to the parametrization of Andreas (1987). Although measurement uncertainties make it difficult to validate this parametrization, a couple of studies support the plausibility of the parametrization at snow-covered sites with z 0 < 10 −3 m (Smeets and van den Broeke 2008; Andreas et al 2010;Park et al 2010;Vignon et al 2017;Liu et al 2020).…”
Section: Monin-obukhov Bulk Parametrizationmentioning
confidence: 99%
“…The roughness lengths for humidity and temperature were calculated as a function of the friction velocity and z 0 according to the parametrization of Andreas (1987). Although measurement uncertainties make it difficult to validate this parametrization, a couple of studies support the plausibility of the parametrization at snow-covered sites with z 0 < 10 −3 m (Smeets and van den Broeke 2008; Andreas et al 2010;Park et al 2010;Vignon et al 2017;Liu et al 2020).…”
Section: Monin-obukhov Bulk Parametrizationmentioning
confidence: 99%
“…The z 0m calculated by Banke and others (1980) is 1.42 × 10 −4 m, and the z 0h ranges from 1.1 × 10 −8 to 1.6 × 10 −4 m according to Andreas (1987). However, Liu and others (2020) analyzed the same dataset employed in this study and revealed that the values of z 0m and z 0h should be 1.9 × 10 −3 and 3.7 × 10 −5 m, respectively. Hence, the values of z 0m and z 0h in the HIGHTSI model are revised according to Liu and others (2020).…”
Section: Resultsmentioning
confidence: 85%
“…However, Liu and others (2020) analyzed the same dataset employed in this study and revealed that the values of z 0m and z 0h should be 1.9 × 10 −3 and 3.7 × 10 −5 m, respectively. Hence, the values of z 0m and z 0h in the HIGHTSI model are revised according to Liu and others (2020). Figures 9a, b compare the parameterized Q h and Q le against the corresponding observations, revealing that Q h is overestimated by the HIGHTSI model, whereas Q le is underestimated.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations